National identity and cultural diversity: A research project that looks at what Year 12 students say about identity in New Zealand: Summary of results - Andrews R; Bell A; Butler P; Tawhai V; Walshaw M (Massey University, 2012)
The aim of the study The aim of the study was to develop an understanding of how young people think of themselves in terms of national identity. The research sought to identify what national identity looks like in New Zealand, how it is fostered, and how young people experience it in everyday life. This summary provides background information of the research and reports on how national identity is broadly conceptualised and experienced by Year 12 students. Background The question of who we are as a people has been a long-standing interest in New Zealand. In 2011 researchers at Massey University, with funding provided by the university, set out to provide an answer to the question from the perspective of young people. Given the bicultural foundations and the multicultural nature of New Zealand the researchers particularly wanted to understand what national identity now looks like, how it is fostered by families, schools, and technological communications, and how it is lived by young people.